1981
DOI: 10.4319/lo.1981.26.1.0172
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of sinking rates of natural copepod and euphausiid fecal pellets1

Abstract: AhstructRecent investigations have demonstrated that the settling velocity, w,, of a cylinder at low Reynolds numbers (the Stokes region) is given bywhere L and D are the cylinder length and diameter, ps is the particle density, and SL. and p are the fluid viscosity and density. This relationship is compared with published data on the settling velocities of cylindrical fecal pellets produced by euphausiids and copepods. The agreement between data and the equation is very good. The analysis further permits the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(93 citation statements)
references
References 12 publications
4
88
1
Order By: Relevance
“…8, the May elutriator results fell between the MarchMay and May-June SV-IRS results. Comparison with other sinking rate calculations-We know of no other settling rate measurements of the sort we describe here, but estimates have been made from observations in the laboratory of phytoplankton and fecal pellet settling, in the field by SCUBA or submersible observation (Komar et al 1981;Shanks and Trent 1980;Asper 1987;Alldredge and Gotschalk 1989;Pilskaln et al 1998), and using marker events in trap fluxes measured at different depths (Honjo and Manganini 1993;Honjo et al 1999;Berelson 2002). Most of these measurements or estimates suggest that particles settle at rates of 70 to 330 m d -1 in the upper 500 m. There is some evidence that particle sinking velocities vary with depth (Honjo and Manganini 1993;Honjo et al 1999), and a recent analysis by Berelson (2002) synthesizing US JGOFS equatorial Pacific and Arabian Sea particle trap data further suggests higher settling rates in deeper (>1000 m) waters.…”
Section: Assessment and Discussionmentioning
confidence: 99%
“…8, the May elutriator results fell between the MarchMay and May-June SV-IRS results. Comparison with other sinking rate calculations-We know of no other settling rate measurements of the sort we describe here, but estimates have been made from observations in the laboratory of phytoplankton and fecal pellet settling, in the field by SCUBA or submersible observation (Komar et al 1981;Shanks and Trent 1980;Asper 1987;Alldredge and Gotschalk 1989;Pilskaln et al 1998), and using marker events in trap fluxes measured at different depths (Honjo and Manganini 1993;Honjo et al 1999;Berelson 2002). Most of these measurements or estimates suggest that particles settle at rates of 70 to 330 m d -1 in the upper 500 m. There is some evidence that particle sinking velocities vary with depth (Honjo and Manganini 1993;Honjo et al 1999), and a recent analysis by Berelson (2002) synthesizing US JGOFS equatorial Pacific and Arabian Sea particle trap data further suggests higher settling rates in deeper (>1000 m) waters.…”
Section: Assessment and Discussionmentioning
confidence: 99%
“…The sinking rates of these different particles can range over several orders of magnitude. For whole phytoplankton, Smayda (1970) has shown that growing cells sink more slowly than senescent cells and that cells with diameters from 1 to 1000 pm respectively sink from 0.01 to 100 m d-l. Representative fecal pellets from copepods and euphausiids sink at sizedependent rates from 10 to 1000 m d-' (Komar et al 1981). These various sinking rates interact with vertical water motion (Titman & Kilham 1976) to determine the residence time of detrital biogenlc silica in the euphotic zone.…”
Section: Latitude Latitudementioning
confidence: 99%
“…A solid matter density of s ϭ 1.23 g cm Ϫ3 represents the wet density of euphausiid fecal pellets (Komar et al 1981), and s ϭ 2.5 g cm Ϫ3 is equal to the density of quartz. When the density of solid particles enclosed in an aggregate is high, the volume ratio ␣/␤ must be larger for aggregates to be neutrally buoyant.…”
Section: Model-based Evaluation Of the Effect Of Tep On The Vertical mentioning
confidence: 99%